Effects of enteral nutrition protocols on nutritional indicators and prognosis in neurological ICU patients: a randomized controlled trial - Xia Zhang; Jun Zhang; Zhi-bo You; Guo-fang Zhang; Ya Chen; Xue-jiao Zhou; Yuan-hua Si; Zhong Luo; Zu-cai Xu; Ben-hai Yao; Piao Cao (Scientific Reports)
Abstract This study investigates the effects of adding whey protein powder and Bifidobacterium quadruplex live bacterial tablets to enteral nutrition on nutritional indicators, complications, and prognosis in neurological ICU patients. Between April 2022 and December 2023, 100 patients requiring enteral nutrition in our hospital’s Neurology ICU were randomly assigned to four groups (25 each): EN1 (enteral nutrition only), EN2 (enteral nutrition + Bifidobacterium), EN3 (enteral nutrition + Bifidobacterium + whey protein), and EN4 (enteral nutrition + whey protein). Nutritional indicators (albumin, total protein, prealbumin), complication rates (diarrhea, constipation, gastric issues), prognosis indicators (hospital stay, ventilator use, lung infections, antibiotic use), and APACHE II scores were compared. This study has been approved by the Ethics Committee of the Affiliated Hospital of Zunyi Medical University, NO: KLL-2021-112. We confirm that all experiments were performed in accordance with relevant guidelines and regulations. After 7 days, EN3 and EN4 groups showed significantly improved nutritional indicators compared to EN1, with EN3 outperforming EN2. Diarrhea and gastric mucosal bleeding were less frequent in EN2 and EN3 compared to EN1 and EN4. APACHE II scores improved significantly in EN3 and EN4 post-treatment. EN3 had the lowest pulmonary infection rate and reduced antibiotic use, but hospitalization time differences were not significant across groups. Metabolic indicators showed no significant differences between groups. Supplementing enteral nutrition with whey protein powder and Bifidobacterium quadruplex improves nutritional status, reduces gastrointestinal complications, and enhances prognosis in critically ill neurological patients. Trial registration: ChiCTR2300079322, (30/12/2023); Website where it was obtained: https://www.chictr.org.cn/bin/home